Factors Affecting the Sheath Losses in Single-Core Underground Power Cables with Two-Points Bonding Method - Osama Elsayed Gouda; Adel Abd-eltwab Farag (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Single-core underground power cables with two-points bonding induce currents in their metallic sheaths. The sheath induced currents are undesirable and generate power losses and reduce the cable ampacity. This paper has shown that the values of the sheath losses in some cases could be greater than conductor losses, depending on various factors. Such these factors are type of cable layouts, cable parameters, cable spacing, sheath resistance, phase rotation, conductor current and cable armoring. In this paper the above factors have been investigated. The calculations are carried out depending mainly on IEC 60287 by a proposed computer program using MATLAB.Keywords: Single-core cables, two-point bonding method, sheaths losses, flat, trefoil, armoringDOI:http://dx.doi.org/10.11591/ijece.v2i1.115